The Personality of the Prophet Moses in the Al-Quran: Study of the Verses of Moses in the Al-Quran Review of Personality Psychology Theory - Ai Syaripah; Eni Zulaiha; Wildan Taufiq (Bulletin of Islamic Research, 2023)
The purpose of the research is to know the structure of the story of Prophet Moses in the Qur'an, the description of his personality viewed from the psychological theory of personality, and the message from the personality of Prophet Moses in the Qur'an. This research uses a literary psychology approach. The method used is the thematic interpretation method, and the type of research is qualitative descriptive analysis. The results of the research on the personality of Prophet Moses in the Qur'an are reviewed from the psychological theory of personality: 1). The division of the structure of the story of Prophet Moses that has been formulated in this research is based on the sequence of the story from the time of his birth to the end of the story in the Quran, including: the first episode, the childhood of Prophet Moses; the second period of adulthood of Moses; the third period of prophethood of Moses; the fourth period of the preaching of Prophet Moses to Pharaoh; the fifth time of his prophethood with the children of Israel regarding the heifer incident; the sixth time of his prophethood with the incident of burying Qarun; and the seventh meeting with Prophet Khidir. 2). The description of Prophet Moses' personality in the Qur'an is reviewed from Allport's personality psychology theory: Moses has a healthy and mature personality. Because all the personality maturity criteria classified by Allport can be found in Moses. Then the personality of Moses, which is reviewed with the personality theory of the Islamic view, is also found in the personality of Moses, which covers Nafs Lawwamah, Muthmainnah Nafs, and an angry soul. 3). Messages from the personality of the Prophet Musa in the Qur'an, as analyzed from each of his journeys, have a message for the life of one of them: that justice requires patience, courage to uphold the truth, a willingness to help, the obligation to fulfill the agreed contract, and patience in spreading religious teachings.